2021
DOI: 10.1038/s42003-020-01584-y
|View full text |Cite|
|
Sign up to set email alerts
|

Partial inhibition of mitochondrial complex I ameliorates Alzheimer’s disease pathology and cognition in APP/PS1 female mice

Abstract: Alzheimer’s Disease (AD) is a devastating neurodegenerative disorder without a cure. Here we show that mitochondrial respiratory chain complex I is an important small molecule druggable target in AD. Partial inhibition of complex I triggers the AMP-activated protein kinase-dependent signaling network leading to neuroprotection in symptomatic APP/PS1 female mice, a translational model of AD. Treatment of symptomatic APP/PS1 mice with complex I inhibitor improved energy homeostasis, synaptic activity, long-term … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(118 citation statements)
references
References 86 publications
11
106
0
1
Order By: Relevance
“…We followed a protocol described previously [ 20 , 21 ]. Briefly, for histopathological analyses, mice were sacrificed and perfused intracardially with 4% paraformaldehyde and cryoprotected in 30% sucrose solution.…”
Section: Methodsmentioning
confidence: 99%
“…We followed a protocol described previously [ 20 , 21 ]. Briefly, for histopathological analyses, mice were sacrificed and perfused intracardially with 4% paraformaldehyde and cryoprotected in 30% sucrose solution.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that mitochondrial ROS-driven glycolytic switch reprograms neuron metabolism in such a way that the production of energy through glycolysis does not match the high energetic demands of the neuron, thus, facilitating its entry into apoptosis. Interestingly, modulation of CI has been associated with development of both PD and Alzheimer's disease (AD; [116][117][118]). Given that CI can undergo activation and deactivation, and both are related to different modes of ROS production, it would be important to ascertain whether the different physiological states of CI are related to the pathogenesis in neurological disorders.…”
Section: Mitochondrial Ros Production In (Patho)physiologymentioning
confidence: 99%
“…AD pathogenesis has been linked to mitochondria as their health is essential in maintaining energy homeostasis and in preventing neuronal dysfunction. Stojakovic et al observed that mitochondrial respiratory chain complex I might be a therapeutic target in AD [ 129 ]. Chronic treatment with complex I inhibitor, the tricyclic pyrone (CP2), which can penetrate the blood brain barrier (BBB) and accumulate in mitochondria, improves cognitive and motor function in transgenic mice, expressing a form of the amyloid precursor protein (APP) and presenilin 1 that leads to early onset AD (APP/PS1).…”
Section: Focus On Experimental Models Of Ad and Potential Antioxidant Therapeutic Targetsmentioning
confidence: 99%
“…Further, this treatment can reduce total Aβ levels triggering autophagy, one of the neuroprotective pathways essential for Aβ clearance. Taken together, the data suggest that CP2 treatment induces multiple protective mechanisms including autophagy, anti-inflammatory, and antioxidant responses, which contribute to reduce Aβ pathology [ 129 ].…”
Section: Focus On Experimental Models Of Ad and Potential Antioxidant Therapeutic Targetsmentioning
confidence: 99%